2010
DOI: 10.2223/jped.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of children with sickle cell disease: a population study

Abstract: Objective: To describe the deaths of children with sickle cell disease (SCD) in Minas Gerais, Brazil, and followed up at the Fundação Hemominas. (March/1998 -February/2005). Deaths were identified by searching for children who did not attend scheduled consultations at hemocenters. Clinical and epidemiological data were abstracted from death certificates, the newborn screening database, individual medical records, and from interviews with families. Methods: Cohort of children diagnosed by the Neonatal Screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 26 publications
3
54
1
9
Order By: Relevance
“…In fact, mortality in this population was found to be 5. % [43]. The importance of integrating neonatal screening in an efective program of care of the patient at a specialized reference center has been more recently conirmed by another recent Brazilian study, which indicated in Minias Gerais State a mortality of .5% patients with SCD in the irst 14 years of life, even though they were undergoing newborn screening, because of a non-efective care program [44].…”
Section: Neonatal Screening For Scd: Major International Experiencesmentioning
confidence: 98%
“…In fact, mortality in this population was found to be 5. % [43]. The importance of integrating neonatal screening in an efective program of care of the patient at a specialized reference center has been more recently conirmed by another recent Brazilian study, which indicated in Minias Gerais State a mortality of .5% patients with SCD in the irst 14 years of life, even though they were undergoing newborn screening, because of a non-efective care program [44].…”
Section: Neonatal Screening For Scd: Major International Experiencesmentioning
confidence: 98%
“…O aumento da morbimortalidade está diretamente relacionado com os determinantes biológicos, todavia, os fatores políticos e sociais podem contribuir de maneira decisiva com a variação desses índices e a qualidade de vida desses indivíduos 1 . Por qualidade de vida compreendem-se as condições de acesso e oportunidades, a escolaridade, habitação, transporte, trabalho, assistência médica, social e apoio familiar.…”
Section: Aspectos Clínicos E Epidemiológicos Da Doença Falciformeunclassified
“…Estima-se que a elevada mortalidade pela doença falciforme no Brasil decorra da pouca efetividade na implementação de políticas públicas. Desse modo, o investimento em educação em saúde, formação profissional, rastreamento dos indivíduos através da triagem neonatal, assistência a familiares de pacientes, melhoria das condições sociais, econômicas e culturais convergem para a redução da morbimortalidade dos indivíduos com doença falciforme 1 .…”
Section: Aspectos Clínicos E Epidemiológicos Da Doença Falciformeunclassified
See 2 more Smart Citations